(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
The objective of this study was to evaluate the inhibitory capacity of Lactiplantibacillus plantarum LP5 against Campylobacter coli in in vitro biofilm formation and competitive exclusion assays. Biofilm formation by C. coli NCTC11366, C. coli DSPV458, C. coli DSPV541 and C. coli DSPV570 was evaluated by OD measurement. The inhibitory capacity of L. plantarum LP5 against C. coli was evaluated on glass, nylon and aluminium discs, added with L. plantarum and incubated at 37°C for 72 h. C. coli was added to each washed well. The plates were incubated at 42°C for 72 h in microaerophilic conditions and the biofilms were detached for quantification. The four strains of C. coli were classified as moderate biofilm former. The competitive exclusion test showed that the biofilm formation of the C. coli strains in all materials was significantly higher than the biofilm formation of each pathogen in the presence of L. plantarum LP5 biofilms. Although it is necessary to carry out more tests to confirm the ability of C. coli to survive in hostile environments until reaching the host, this study would allow progress in the elucidation of its behaviour through the formation of biofilms.